Vitamin D (25 ( OH) D ) in patients with chronic kidney disease stages 2-5 (Colombia Medica, 2019)
This corrects the article "Vitamin D (25 ( OH) D ) in patients with chronic kidney disease stages 2-5" in volume 47(3) on page 163, Table 3.The September 30, 2016, article by Restrepo and Aguirre (Colomb Med (Cali). 2016;47(3): 160-6, was published with errors in Table 3.In body of Table 3, the sixth line of the first column entitled PH (pg/mL), this should read: PTHi (pg/mL).The sixth line of the eight column reads: 11.65, this should read: 116.5. That date appears well in the English XML version, but in both the PDF ingles and the Spanish version appears the value 11.65, must be changed to the real value: 116.5.